FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK MENGGUNAKAN JASA KONSULTAN PAJAK - Novi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The purpose of this research is to examine and analyze the factors that influence individual taxpayers using the services of the Nurmalasari Tax Consultant in Surakarta with variables: taxpayer motivation, taxpayer sanctions, taxpayer perceptions, knowledge of taxation, quality of tax consultants. The research population is 250 individual taxpayers at KKP Nurmalasari. The sampling technique is random sampling using Roscoe's theory found 71 taxpayer respondents with multiple linear regression analysis model. Based on the results of this study, the motivation of taxpayers, tax sanctions and the quality of tax consultants have an effect on the use of Tax Consulting Services, taxpayer perceptions and knowledge of taxation have no effect on the use of Tax Consulting Services. The limitation of this research is that it cannot be generalized. The suggestion in this study is that further researchers can use taxpayers at KKP in the Surakarta area. Keywords: Tax Consulting Services, Taxpayer Motivation, Taxpayer Sanctions, Taxpayer Perceptions, Tax Knowledge, Tax Consultant Quality.